Occupational Accidents and Occupational Health and Safety Management Systems ISO 45001:2018 in EU (Journal of Universal Excellence, 2026)
Research Question (RQ): Occupational health and safety (OH&S) is an important cornerstone of social development and one of the key elements of modern organizations’ operations. Therefore, our primary research question was whether the number of organizations with the ISO 45001:2018-certified OH&S system affects the number of accidents at work in EU member states.Purpose: The primary purpose of our research was to obtain the answer to our research problem. In addition, the research examined possible correlations between accidents at work, number of employed persons in EU member states and number of organizations certified to ISO 45001:2018.Method: The analysis was based on the Eurostat data on the number of accidents at work and the number of employed persons in the 27 EU member states, as well as on data of International Organization for Standardization, on the number of organizations certified to ISO 45001:2018 in 2020. The ESAW methodology was applied to calculate the incidence rate and the ISO 45001:2018 certificate rate. Statistical processing of numerical data was done by means of the Minitab software, while the obtained results are shown in bar charts. The set hypotheses were tested by calculating the Spearman’s correlation coefficient »rs« and by regression analysis.Results: In 2020, 2,738,920 accidents at work were recorded in EU member states, 3,355 of which were fatal. In absolute terms, the highest number of non-fatal accidents was observed in Germany, while the number of fatal accidents was the highest in Italy. The highest incidence rate of non-fatal accidents was recorded in Denmark, while that of fatal accidents was observed in Cyprus. In 2020, there were 30,849 organizations in the EU with the OH&S system certified to ISO 45001:2018, with Italy being the country with the highest number of certificates issued per 100,000 employed persons. It was established that there is a correlation between the number of accidents at work, number of employed persons, number of ISO 45001:2018 certificates, incidence rate and ISO 45001:2018 certificate rate. The main finding of our research is that the number of organizations certified to ISO 45001:2018 does affect the number of accidents at work in EU member states. An increase in the number of certified organizations results in a decrease in the incidence rate.Organization: The research provides information on the number of accidents at work and the number of issued ISO 45001:2018 certificates in EU member states. However, the major finding for organizations is that by implementing the OH&S management system certified to ISO 45001:2018 they can reduce the number of accidents at work. The results of our research may stimulate non-certified organizations to obtain certification.Society: The findings of our study can provide a basis for society and, in particular, legislators to strengthen the measures in terms of incentives for organizations to opt for ISO 45001:2018 certification of their OH&S systems, resulting in the reduction of accidents at work.Originality: The study examined the current 27 EU member states and was based on the latest publicly available Eurostat data on accidents at work in 2020. In terms of exploring the impact of the OH&S management system certified to ISO 45001:2018 on the number of accidents at work, our study is the first of its kind in the EU.Limitations / further research: The study was limited to the EU area and the latest publicly available Eurostat data on accidents at work in 2020, which were only studied in terms of non-fatal and fatal accidents. It would be useful to extend the study to the geographical area of Europe and to address the industries in which organizations operate. In particular, we suggest that the analysis be conducted over several consecutive years, which would enable the study of the trend of the effect of the ISO 45001:2018-certified OH&S system on the number of accidents at work.
Keywords: accidents at work; ISO 45001:2018; incidence rate; European Union; occupational health and safety management system